The assessment of sleep in pediatric chronic pain sufferers. - De la Vega, Rocío; Miró, Jordi (Elsevier, 2013)
The aim of this study is to review the options available for assessing sleep in pediatric chronic pain populations. One subjective measure of sleep (questionnaires) and two objective measures (polysomnography and actigraphy) were reviewed. The following databases were searched from their inception to June 2011: PsycINFO, ERIC, FRANCIS, MEDLINE, PsycARTICLES, Global health, Inspec, Health and Psychosocial Instruments, CINAHL, Scopus and ProQuest Dissertations and Theses databases. A total of nine sleep questionnaires were identified, two of which proved to be reliable and valid when used with pediatric chronic pain patients and, according to evidence-based assessment criteria, can be regarded as “well-established” instruments. Objective measures have been used less frequently. Both polysomnography (PSG) and actigraphy (ACT) have been used in five different studies. PSG is a reliable method for assessing sleep stage problems but is costly and intrusive. Actigraphy is cheaper, more ecological and easier to use than PSG but it deals only with the objective dimension of sleep (total sleep time, sleep efficiency, etc). In order to improve the reliability and validity of the assessment of sleep, a multi-level and multimethod approach is suggested: sleep measurement should be extended to include both objective and subjective assessment.
https://openpolicyfinder.jisc.ac.uk/id/publication/12948
Keywords: Dolor crónico - Niños; Sueño; Pediatría; Sleep; Chronic pain; Assessment; Children; Adolescents; Questionnaire; Polysomnography; Actigraphy; Pediatric